A kinematic-dual snake robot: Undulatory mobile robot driven by controllable side-thrust links. (April 2023) - Takagi, Yuki; Ishikawa, Masato; Osuka, Koichi
Abstract: This paper introduces the notion of a kinematic-dual snake robot, as contrasted with a conventional wheeled snake robot. The well-known original snake robot consists of active joints, passive wheels, and corresponding side-slip constraints. The purpose of this study is to present a string-like mobile mechanism as a solution to the difficulty of manipulating the original snake. The key idea in devising the proposed snake is to reverse the mechanical elements of the original snake and then refine the reversed mechanism by the kinematics so that it is a dual system of the original snake. Thus, the proposed snake consists of passive joints and active omnidirectional wheels plus two ordinary wheels at the ends, associated with side-slip constraints. Here, we introduce the concept of the kinematic-dual snake and explain in what sense it is kinematic-dual . Then, through controllability analysis, motion planning, and experiments, we prove that the concept of the kinematic-dual snake is reliable as a mobile mechanism. The proposed robot can improve its manipulability while maintaining the advantages of the string-like body. The authors expect this idea would contribute to tasks that require both joint angle manipulation and traveling, such as transportation with wrapping around an object.